A Chart of Accounts as a Tool for the Implementation of Accounting Principles (Policies) in an Investment Fund - Szczepankiewicz , Elżbieta-Izabela (Studia Oeconomica Posnaniensia, 2014)
Almost six hundred investment funds operate in Poland. To date, the Ministry of Finance has not developed a standard chart of accounts for such funds. This article discusses the principles of construction as well as the structure and the scope of a chart of accounts for an investment fund, which is the primary tool for implementing the accounting principles (policies) of the fund. Based on an analysis of the available literature, the legal regulations as well as internal materials from investment funds, the article proposes a standard chart of accounts for an open-ended investment fund.